2023
DOI: 10.2147/dmso.s427412
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the MIND Diet with Cardiometabolic Diseases and Their Risk Factors: A Systematic Review

Zoha Akbar,
Sundus Fituri,
Asma Ouagueni
et al.

Abstract: Purpose Recent studies have expanded the scope of research on the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet beyond its impact on cognitive performance. These investigations have specifically explored its potential to provide protection against cardiometabolic diseases and associated risk factors, including obesity and dyslipidemia. Methods We systematically summarized and evaluated all existing observational and trial evidence for the MIND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Finally, excessive consumption of these AS-rich CHO foods and beverages may result in a higher risk for MetS and its components due to overall poor diet quality, 40 as opposed to healthy diet patterns, including a Mediterranean, dietary approach to stop hypertension (DASH), Mediterranean-DASH intervention for neurodegenerative delay, or other plant-based diet pattern, that protects cardiometabolic health. 41 , 42 High AS intake in this study and others was related to poor diet quality, as represented by a lower HEI2015 score, characterized by low intakes of whole grain products, fruit, and vegetables, thus resulting in lower intakes of fibre and micronutrients (i.e. iron, zinc, magnesium, folate, and other vitamins and minerals).…”
Section: Discussionmentioning
confidence: 49%
“…Finally, excessive consumption of these AS-rich CHO foods and beverages may result in a higher risk for MetS and its components due to overall poor diet quality, 40 as opposed to healthy diet patterns, including a Mediterranean, dietary approach to stop hypertension (DASH), Mediterranean-DASH intervention for neurodegenerative delay, or other plant-based diet pattern, that protects cardiometabolic health. 41 , 42 High AS intake in this study and others was related to poor diet quality, as represented by a lower HEI2015 score, characterized by low intakes of whole grain products, fruit, and vegetables, thus resulting in lower intakes of fibre and micronutrients (i.e. iron, zinc, magnesium, folate, and other vitamins and minerals).…”
Section: Discussionmentioning
confidence: 49%
“…MIND diet for other health outcomes ( 11 , 15 , 42–51 ), including CVDs, cancer, and diabetes. Akbar et al ( 52 ) conducted a systematic review to investigate the relationship between the MIND diet and cardiometabolic diseases and risk factors, and they concluded that the MIND diet may be an effective dietary pattern to reduce cardiometabolic risk. Tison et al ( 53 ) conducted a prospective study to explore the association between some diets of Mediterranean diet, MIND diet, and DASH diet and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary habits have been implicated in many human diseases, including CSVDs [ 383 - 385 ]; similarly, a healthy diet is considered to have protective benefits against LA. Two studies—a population-based longitudinal study and a cross-sectional study—showed that dietary interventions can decrease WMH severity and delay LA progression [ 386 , 387 ].…”
Section: Management Of Lamentioning
confidence: 99%